Joëlle Tuerlinckx : This book like a book. - Hundsblicher, Gottfried; Tuerlinckx, Joëlle; Exhibition. Joëlle Tuerlinckx : This book like a book (1). Exhibition. Joëlle Tuerlinckx : This book like a book (2). Le Collège, FRAC (Fonds Régional d'Art Contemporain) Champagne-Ardenne Reims. SMAK (Stedelijk Museum voor Actuele Kunst) Gent. 1999-01-07. 1999-04-01. 1999-02-07. 1999-05-31 (Gent : Museum van Hedendaagse Kunst Gent, 1999)
This book, like a book is for all those who are interested in it, it serves as a reference volume to the other volumes of the collection B.O.O.K. B.O.O.K. consists of indexed volumes of bound photocopies, the format of which is the same as 'this book - basic book vol.0' the material remains unprocessed and comprises : texts describing exhibitions, titles, fragments of titles and words of titles, cartons of titles, fragments of text, title-cartons, inventories of materials, concise descriptions, extensive descriptions, correspondance with museums, art centres and galleries, measures to be taken to preserve the works, complaints, dialogues and extracts of dialogues, extracts of private texts, photographs and various reproductions,...
Joëlle Tuerlinckx, Stedelijk Museum voor Actuele Kunst, Gent, 7 januari 1999- 7 februari 1999
timetable listing (tent.& manifestaties) p. 73-75, collection listing (bibliog.) p. 77-80
Engels
Frans
Nederlands
boek
Keywords: Tuerlinckx, Joëlle